PENGARUH TERAPI MUSIK DANGDUT TERHADAP TINGKAT STRES PADA LANSIA - Siti Zakiyah; Nurwijaya Fitri; Nova Mardiana; Tasya Anggraini (Citra Internasional Institute, 2024)
Aging is a natural process experienced by everyone and at this stage, the body experiences various changes both physically, mentally, and socially. Dangdut music therapy is very important to create a sense of calm for the elderly, because dangdut music can stimulate the brain system related to emotional nerves. This study aims to determine the effect of dangdut music therapy on stress levels in the elderly. This research method is a quantitative pre-experimental study with a one-group pretest-post-design method. Data collection was carried out using a questionnaire and dangdut music therapy was given. The sample in this study was 28 people. This data was analyzed using the Paired Samples Test. The results of this study showed that there was an effect of dangdut music therapy on stress levels in the elderly at Panti Bhakti Kasih Siti Anna Pangkalpinang with a p-value of the first intervention of 0.006 and a p-value of the second intervention of 0.000 (<0.05). The suggestion from this study is that it is expected to be a guideline for increasing the role of nurses and elderly people in providing dangdut music therapy for the elderly to reduce stress levels.